Could lowering the tackle height in rugby union reduce ball carrier inertial head kinematics? - Tierney, G. J.; Richter, C.; Denvir, K.; Simms, C. K. (Journal of Biomechanics, 2018)
There is mounting evidence of reduced long-term cognitive ability in rugby players, even in those without a reported history of concussion. The tackle height law is an area of controversy. However, little is known about the effects of repetitive inertial head loading in rugby. Furthermore, the magnitude and influencing factors for head kinematics are generally unknown. In this exploratory study, 45 multibody front-on shoulder tackles simulated with the MADYMO pedestrian model and 20 staged rugby tackles executed by professional rugby players in a marker-based 3D motion laboratory were used to assess the effect of tackle height on ball carrier head kinematics. The peak resultant head linear accelerations, angular accelerations and change in angular velocities were measured and examined. The results suggest that tackle height strongly affects the head kinematics experienced by the ball carrier. In particular, higher ball carrier head kinematic values were identified for upper trunk tackles compared to mid/lower trunk tackles in both the multibody simulations and the staged rugby tackles. Average ball carrier peak resultant head linear acceleration, angular acceleration and change in angular velocity values for upper trunk tackles were greater than for mid/lower trunk tackles by a factor of 1.5, 2.5 and 1.7, in the multibody simulations, respectively, and 1.8 (p = 0.102), 2.2 (p = 0.025) and 2.3 (p = 0.004), in the staged tackles, respectively. The results of the study support the proposition of lowering the current tackle height laws to below the chest.